USABILITY ICON EVALUATION OF SEI/UFCG VISUAL INTERFACE FROM A HIBRID APPROACH (Human Factors in Design, 2022)
This article is a result of a Masters research on the usability evaluation of icons that compose a visual interface of the Information Electronic System used for UFCG. The data was obtained by 78 professors from the UFCG campus, from the use of two online forms, first to identify the spontaneous understanding of the icons and the second one from the creation of the semantic differential scale using usability quality indicators from Galitz (2007). In a conclusion, it was reached out that only 18% of icons had a good comprehension and all of the others had the understanding compromised.
Keywords: user centric design; usability; icon; SEI-UFCG